Just living : poems and prose by the Japanese monk Tonna - Ton'a, 1289?-1372? (Columbia University Press, 2003)
One of the best scholar-translators in the field presents a selection of writings by Tonna (1289--1372), an outstanding medieval Buddhist poet-monk, very little of whose work has been translated until now. Tonna was regarded as the leading Nijo ̄ poet of his day and was known as one of the Four Deva Kings of the Waka. This anthology contains translations of 134 uta, 16 linked-verse couplets, and selections from a prose narrative, From a Frog at the Bottom of a Well, along with an introduction and explanatory notes, a glossary of important names and places, and a list of sources.
Keywords: Ton'a, -- 1289?-1372? -- Translations into English.; Ton'a, -- 1289?-1372?; LITERARY CRITICISM -- Asian -- General.; LITERARY COLLECTIONS -- Asian -- General.; Electronic books.; poetry.; Translations; Vertalingen (vorm); Gedichten (teksten); Poetry.; Poésie.